Innovative concepts in diet therapies in disorders of gut–brain interaction - Daniel So; Caroline Tuck (JGH Open, 2024)
Abstract Diet therapy in disorders of gut–brain interaction (DGBI) is rapidly advancing, with accumulating evidence to support two innovative therapies—manipulation of dietary fibers and enzyme supplementation—that target specific DGBI pathophysiology and modulate digestion. Dietary fibers escape digestion in the upper gastrointestinal tract and can influence gut function by impacting digestion, improving laxation, and interacting with the microbiota. A more nuanced understanding of different fiber types and their ability to impact gut function in highly specific ways has shown that fibers can impact distinct gut symptoms and pathophysiology. By considering their functional characteristics of bulking, gel‐forming, and fermentability, restriction or supplementation of specific fibers can offer clinical value in DGBI. Similarly to fiber specificity, emerging evidence suggests that supplemental digestive enzymes may be targeted to known food triggers with consideration that enzymes are substrate specific. Limited evidence supports use of lactase to target lactose, and α‐galactosidase to target galacto‐oligosaccharides. Application of enzymes during manufacturing of food products may prove to be an additional strategy, although evidence is scant. Both innovative therapies may be utilized in isolation or in combination with other diet and nondiet therapies. Implementation can be guided by the principles that fiber modulation can be targeted to specific symptomology or requirement for alterations to gut function, and digestive enzymes can be targeted to known food triggers. This review aims to summarize recent literature of these two innovative concepts and provide practical suggestions for their implementation in clinical practice.